Integration of Health Coaching Concepts and Skills into Clinical Practice Among VHA Providers: A Qualitative Study - David A. Collins; Kirsten Thompson; Katharine A. Atwood; Melissa H. Abadi; David L. Rychener; Leigh Ann Simmons (SAGE Publishing, 2018)
Background Although studies of health coaching for behavior change in chronic disease prevention and management are increasing, to date no studies have reported on what concepts and skills providers integrate into their clinical practice following participation in health coaching courses. The purpose of this qualitative study was to assess Veterans Health Administration (VHA) providers' perceptions of the individual-level and system-level changes they observed after participating with colleagues in a 6-day Whole Health Coaching course held in 8 VHA medical centers nationwide. Methods Data for this study were from the follow-up survey conducted with participants 2 to 3 months after completing the training. A total of 142 responses about individual-level changes and 99 responses about system-level changes were analyzed using content analysis. Results Eight primary themes emerged regarding individual changes, including increased emphasis on Veterans' values, increased use of listening and other specific health coaching skills in their clinical role, and adding health coaching to their clinical practice.Four primary themes emerged regarding system-level changes, including leadership support, increased staff awareness/support/learning and sharing, increased use of health coaching skills or tools within the facility, and organizational changes demonstrating a more engaged workforce, such as new work groups being formed or existing groups becoming more active. Conclusions Findings suggest that VHA providers who participate in health coaching trainings do perceive positive changes within themselves and their organizations. Health coaching courses that emphasize patient-centered care and promote patient-provider partnerships likely have positive effects beyond the individual participants that can be used to promote desired organizational change.